Whale sightings during POLARSTERN cruise PS135/1 - Elke Burkhardt (PANGAEA, 2024)
Data on whale distribution and abundance in the polar oceans is rather sparse, as implementing the standard surveying method, line-transect surveys, is challenging and costly. To overcome this problem, we initiated a program to electronically log all opportunistic cetacean sightings during all Polarstern expeditions through the nautical officer on watch. Opportunistic (visual) sightings by naked eye were logged during Polarstern Cruise PS135/1 (Punta Arenas - Mindelo) by the nautical officer on duty using a customized Software package (WALOG, WhAleLOGger) installed on a touch screen laptop located on the ship extquotesingles bridge. Species were identified by naked eye or handheld binoculars (7x50) to the lowest possible taxonomical level and assigned a "certainty" level of identification. The number of animals were counted if possible or estimated for larger groups. Whenever identification to species level was not possible, the next identifiable taxonomical category was assigned. Information on sighting position, date and time are automatically transferred from the ship extquotesingles DAVIS-Ship System (https://dship.awi.de/) to the WALOG software at the time of logging. Photographs were taken, if possible, for retrospective analysis. All data of acquired sightings were retrospectively validated by a marine biologist and converted to a standard format. To this end, plausibility of sighting time, location, standardization of species names, eventual comments added at the time of sighting, as well as additional information such as photographs (if available) were checked either to verify or improve species identification. Datasets are used in species distribution modelling and to inform interested parties about occurrences.